Determinants of intercorporate investments: An empirical investigation of Indian firms - Vedika Saxena; Seshadev Sahoo (International Journal of Financial Studies, 2021)
We examine the determinants of intercorporate investments for a sample of 127 firms listed in the National Stock Exchange (NSE) in India for the period 2015-2019. This research indicates that the investor firm's intercorporate investments are influenced by free cash flows, dividend yield, promoter holding, and leverage. Interestingly, contrary to anecdotes in the financial press, the investor firms where promoter holding (equity) is more, prefer to invest less in the other firm's capital (as part of intercorporate investment). Using OLS regression, this analysis does not find evidence for the variables, that is, the firm's age, the capital expenditure required, growth in earnings per share, board independence, and CEO duality for significant influence on intercorporate investments. Further tests for industry effect reveal the consumer and retail sector's intercorporate investments to be significantly different (i.e., lower) from the manufacturing and service sectors.
Keywords: G3; G300; G390; 330; board independence; capital expenditure; earnings per share; free cash flows; intercorporate investments; leverage